Impact on gait biomechanics of using an active variable impedance prosthetic knee. Issue 1 (December 2016) - Williams, Matthew; D'Andrea, Susan; Herr, Hugh
Abstract Background An above knee amputation can have a significant impact on gait, with substantial deviations in inter-leg symmetry, step length, hip exertion and upper body involvement even when using a current clinical standard of care prosthesis. These differences can produce gait that is less efficient and less comfortable, resulting in slower and shorter distance walking, particularly with long term use. Methods A robotic variable impedance prosthetic knee (VI Knee) was tested with five individuals (N  = 5) with unilateral amputation above the knee at fixed speeds both above and below their normal walking speed. Subject gait was measured as they walked along an instrumented walkway via optical motion capture and force plates in the floor. Each subject's gait while using the VI Knee was compared to that while using their standard of care knee (OttoBock C-Leg). Results Significant differences (p < 0.05) in walking between the standard of care and variable impedance devices were seen in step length and hip range of motion symmetries, hip extension moment, knee power and torso lean angle. While using the VI Knee, several subjects demonstrated statistically significant improvements in gait, particularly in increased hip range of motion symmetry between affected and intact sides, greater prosthesis knee power and in reducing upper body involvement in the walking task by decreasing forward and affected side lean and reducing the pelvis-torso twist coupling. These changes to torso posture during gait also resulted in increased terminal stance hip flexion moment across subjects. Detriments to gait were also observed in that some subjects exhibited decreased step length symmetry while using the VI Knee compared to the C-Leg. Conclusions The knee tested represents the potential to improve gait biomechanics and reduce upper body involvement in persons with above knee amputation compared to current standard of care devices. While using the VI Knee, subjects demonstrated statistically significant improvements in several aspects of gait though some were worsened while using the device. It is possible that these negative effects may be mitigated through longer term training and experience with the VI Knee. Given the demonstrated benefits and the potential to reduce or eliminate detriments through training, using a powered device like the VI Knee, particularly over an extended period of time, may help to improve walking performance and comfort.